The Curriculum's Effectiveness in Technical and Vocational Education and Training (TVET): A Case Study of the National Vocation Institute in Battambang, Cambodia - Heng, Ngounhort; Thanakyuth, Sal Vichea; Try, Chanthuch; Sou, Veasna (Archives of Business Research, 2025)
This manuscript investigates the preparation of Cambodian students for job opportunities and their satisfaction with vocational and training institutions through the use of virtual experiences. This study involved 234 Cambodian students evaluating the quality of the TVET curriculum and career satisfaction from the BIT (Battambang Institute of Technology) and NVIB (National Vacation Institute of Battambang) in Battambang province, as well as an additional 244 students who participated in a separate study assessing the effectiveness of the TVET program in meeting current labor market demands. Through a self-administered structured questionnaire, we recorded students' experiences with vocational and training institutions to meet and satisfy their career opportunities based on the needs and demands of the labor market. The ANOVA results indicate that students from both BIT (Battambang Institute of Technology) and NVIB (National Vocational Institute of Battambang) perceived that participating in the vocational training program enhanced their job satisfaction, as it prepared them for the industry's needs. Therefore, this manuscript also provides detailed coverage of further research findings.